Corn Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas; Martin, Kent L. (My University, 2009)
This publication provides estimated cost and returns for forward farm planning for corn in south central Kansas.
MF2157_2009_12
Keywords: MF2157; Crops; Economics; MF